2020
DOI: 10.22271/chemi.2020.v8.i6x.11001
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy of insecticides against tomato fruit borer, Helicoverpa armigera (Hubner)

Abstract: Selected insecticides viz. Flubendiamide 39.35% SC, Indoxacarb 14.5% SC, Lambda cyhalothrin 5% EC, Novaluron 10% EC, Quinalphos 25% EC, Spirotetramat 120% SC+ Imidacloprid 120% SC Chlorantraniliprole 18.5% SC were evaluated for their effectiveness against tomato fruit borer by conducting field trial at PGI, MPKV, Rahuri during the year 2019. Three sprays of each insecticide were applied at the occurrence of the pest. The result revealed that lowest larval population (1.14 larvae/plant) of H. armigera was recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Kumar (2013) investigated several pesticide treatments and discovered that profenophos 50 EC at 1 000 g a.i./ha, emamectin benzoate 5 SG at 22 g a.i./ha, and bifenthrin at 100 g a.i./ha decreased the fruit borer populations and reduced the fruit damage by a factor of 100. Babu and Singh (2015) demonstrated the efficiency of chlorantraniliprole 18.5 SC in the management of H. amigera when compared to other compounds. Mourya et al (2015) found that spinosad and imidacloprid were the most and least effective insecticides against the tomato fruit borer, respectively.…”
Section: H Armigeramentioning
confidence: 96%
See 2 more Smart Citations
“…Kumar (2013) investigated several pesticide treatments and discovered that profenophos 50 EC at 1 000 g a.i./ha, emamectin benzoate 5 SG at 22 g a.i./ha, and bifenthrin at 100 g a.i./ha decreased the fruit borer populations and reduced the fruit damage by a factor of 100. Babu and Singh (2015) demonstrated the efficiency of chlorantraniliprole 18.5 SC in the management of H. amigera when compared to other compounds. Mourya et al (2015) found that spinosad and imidacloprid were the most and least effective insecticides against the tomato fruit borer, respectively.…”
Section: H Armigeramentioning
confidence: 96%
“…larval population of H. armigera of 1.05 larvae/5 plants was noted in the treatment with pyridalyl at 150 g a.i./ha which reduced the damage up to the extent of 84.19%. According to Safna et al (2018a), chlorantraniliprole 18.5 SC at 0.005% was the best with the least amount of fruit infestation (13.82%), followed by spinosad (17.39%), indoxacarb 14.5 SC at 0.012% (21.64%) and lambda cyhalothrin 5 EC 0.0025% (23.50%). Swodesh and Bhishma (2019) investigated several chemicals and discovered that flubendiamide 40SC at 0.21 mL/L and emamectin benzoate were both efficient against the tomato fruit borer.…”
Section: H Armigeramentioning
confidence: 99%
See 1 more Smart Citation